Business Students’ Assessment of Attitudes and Readiness Towards Online Education - Eric S Parilla; Marc Edward M Abadilla (Applied Quantitative Analysis, 2021)
The study investigates the association of students’ attitudes towards online education and learners’ readiness to online education. The study's participants were students from Ilocos Norte's seven main universities and colleges, who were chosen via a convenience sample approach. The study used a quantitative research design and an informal research technique to determine the association between students' views regarding online education and their readiness to learn. Using linear regression, the findings revealed a positive relationship between the attitudes and learners’ readiness towards online education Moreover, concerning the moderating effect of the demographic profile, using moderation analysis by Jamovi, the results was moderating effect of year level to the relationship of the two variables. This study answered the research gap of trying to find answer on the question whether there is a relationship between students’ attitudes towards online education and their readiness. Students with positive attitude towards online education are more prepared and ready than learners’ who have negative behavior towards online education. The research also included implications, findings, and suggestions.